2y+18=-6y

Simple and best practice solution for 2y+18=-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2y+18=-6y equation:


Simplifying
2y + 18 = -6y

Reorder the terms:
18 + 2y = -6y

Solving
18 + 2y = -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
18 + 2y + 6y = -6y + 6y

Combine like terms: 2y + 6y = 8y
18 + 8y = -6y + 6y

Combine like terms: -6y + 6y = 0
18 + 8y = 0

Add '-18' to each side of the equation.
18 + -18 + 8y = 0 + -18

Combine like terms: 18 + -18 = 0
0 + 8y = 0 + -18
8y = 0 + -18

Combine like terms: 0 + -18 = -18
8y = -18

Divide each side by '8'.
y = -2.25

Simplifying
y = -2.25

See similar equations:

| 7(x-3)=5x | | 1-2(x+2)=-10x-35 | | 4k+16=4(k+4) | | -8n-7=24 | | 2x-7=1/2(3x-6) | | 21+9c=4(7c-3) | | 8=x^2-7x+3 | | -4(z+3)+7=4z+3 | | 0=3x+(-2) | | 8.8x=167.2 | | 16b+8=-8 | | 14=28+7(1-x) | | -6+10k=74 | | X+7+3x=-17-9 | | 6z-6=22+4z | | 6x^4-x^2-15= | | 4(x-3)-5x=2 | | 9c^2-17c-2=0 | | 2+t=3*2+4 | | t-18+9=11 | | 6=5n-6n | | -2(r+3)=8 | | 3/5z=-6 | | Y=x^3/x-1 | | -3(2x-4)=4(3/2x-3) | | 2x^6+x^3-28= | | 5(n+4)=85 | | 5+g+7=6+5+5 | | 9-(6+3n)= | | n/8-3=-33 | | 5(n+4)=70 | | 1/3k=1 |

Equations solver categories